An autoethnography of a peace educator: Deepening reflections on research, practice and the field. (August 2018) - Cremin, Hilary
Highlights: Peace educators and researchers benefit from integrating emotion, embodiment, aesthetics and spirituality into their work. Experimental research and writing methods, such as autoethnography and poetry, deepen analysis and findings. Understanding of complexity and eco-systems supports evaluation of peace education in schools. Space, time and emotion intersect to create meaning and change.